Postpartum haemorrhage (PPH) rates in randomized trials of PPH prophylactic interventions and the effect of underlying participant PPH risk: a meta-analysis - Lydia Hawker; Andrew Weeks (BMC, 2020)
Abstract Background Postpartum haemorrhage (PPH) remains a leading cause of maternal mortality. Many trials assessing interventions to prevent PPH base their data on low risk women. It is important to consider the impact data collection methods may have on these results. This review aims to assess trials of PPH prophylaxis by grading trials according to the degree of risk status of the population enrolled in these trials and identify differences in the PPH rates of low risk and high risk populations. Methods Systematic review and meta-analysis using a random-effects model. Trials were identified through CENTRAL. Trials were assessed for eligibility then graded according to antenatal risk factors and method of birth into five grades. The main outcomes were overall trial rate of minor PPH (blood loss ≥500 ml) and major PPH (> 1000 ml) and method of determining blood loss (estimated/measured). Results There was no relationship between minor or major PPH rate and risk grade (Kruskal-Wallis: minor - T = 0.92, p = 0.82; major - T = 0.91, p = 0.92). There was no difference in minor or major PPH rates when comparing estimation or measurement methods (Mann-Whitney: minor - U = 67, p = 0.75; major - U = 35, p = 0.72). There was however a correlation between % operative births and minor PPH rate, but not major PPH (Spearman r = 0.32 v. Spearman r = 0.098). Conclusions Using data from trials using low risk women to generalise best practice guidelines might not be appropriate for all births, particularly complex births. Although complex births contribute disproportionately to PPH rates, this review showed they are often underrepresented in trials. Despite this, there was no difference in reported PPH rates between studies conducted in high and low risk groups. Method of birth was shown to be an important risk factor for minor PPH and may be a better predictor of PPH than antenatal risk factors. Women with operative births are often excluded from trials meaning a lack of data supporting interventions in these women. More focus on complex births is needed to ensure the evidence base is relevant to the target population.